SIFAT MEKANIK BAHAN KOMPOSIT KAMPAS REM BERBAHAN DASAR SERBUK ARANG KULIT BUAH MAHONI - Herwidhi Tri Prabowo; Sulhadi Sulhadi; Mahardika Prasetya Aji; Teguh Darsono (Spektra: Jurnal Fisika dan Aplikasinya, 2017)
Mahogany bark is one of natural material which not used optimally in society. The overabundance of mahogany bark appearing new problem of garbage which charges an alternative solution creatively and innovatively becomes a new efficient and effective product. An alternative solution of mahogany bark utilization is as organic composite material of disk brake. The making of organic composite material of brake disk firstly is reducing the mahogany bark becomes a homogeneous carbon powder. The mahogany bark was smoked being of carbon and mixed with coconut shell and resin polyester as an adhesive. The organic composite material was produced, tested by Brinell Hardness test and attrition test by varied of composition percentage. There are five kinds of composite material composition had been tested. The result is obtainable of the most precise composition percentage 60% mahogany bark carbon, 15% coconut shell carbon, and 25% resin polyester which has brinell hardness number and attrition massa identically with Standar Nasional Indonesia (SNI). Keywords: mahogany bark, composite material, disk brake, Brinell hardness test, attrition test